Effect of pre-slaughter withdrawal from feed on cattle fasted for varying lengths of time - T. Carr; Dell M. Allen; P. Phar; R. Cox (Kansas Agricultural Experiment Station Research Reports, 1969)
Feedstuffs pass through cattle in approximately four days; however, steam-flaked rations may have a faster rate of passage. How much value do cattle derive from feed fed the last few days prior to slaughter, particularly cattle taken directly from feedlot to slaughter plant? Cattle that have been shrunk kill more easily than those with full intestinal tracts. Perhaps withdrawing cattle from feed 1, 2, or 3 days before they are slaughtered would economically benefit both feeder and slaughterer.
Keywords: Cattlemen& #x27; s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; Steam-flaked rations; Feedlot; Carcass yield